Elevated basophils in peripheral blood predict lower extremity deep venous thrombosis in non-surgical patients with spontaneous intracerebral hemorrhage - Chu-Bin Liu; Bao-Fang Wu; Liang-Qin Luo; Jia-Yin Wang; Wei-Peng Hu; Xin-Tong Zhang; Hong-Zhi Gao (Scientific Reports)
Abstract Leukocytes are associated with lower extremity deep venous thrombosis (LEDVT) in patients with spontaneous intracerebral hemorrhage (sICH). Nonetheless, the correlation between differential leukocyte subtype counts in peripheral blood and LEDVT is poorly understood. This study explored the relationship between admission basophils in leukocytes and 14-day LEDVT in non-surgical patients with sICH. This retrospective observational study was conducted at a single institution on consecutive patients who were diagnosed with sICH between January 2021 and August 2023. The primary outcome was detecting LEDVT occurrence within 14 days from the onset of the acute sICH episode. Weighted logistic regression models were employed to estimate the association between blood basophil level and LEDVT. Out of 315 patients with sICH who met the inclusion criteria, 47 (14.92%) experienced LEDVT. The cut-off blood basophil levels measured upon admission from the receiver operating characteristic (ROC) curve showed that peripheral blood basophil counts ≥ 100 /µL were considered basophil-rich. After adjusting for potential variables, the weighted multivariable logistic regression analysis revealed that the occurrence of LEDVT in sICH patients with basophil-rich status was 2.7 times more likely to experience LEDVT compared to those with basophil-poor status (odds ratios:2.7, 95% confidence intervals [1.1–6.8], P = 0.032). Elevated basophils in the peripheral blood upon admission independently predict the occurrence of LEDVT in non-surgical sICH patients.